Interface shear strength at various joint types in high-strength precast concrete structures - Kim, Young Jin; Chin, Won Jong; Jeon, Se Jin (Materials, 2020)
More precast concrete structures have recently been constructed due to their many advantages when compared to conventional cast-in-place construction. Structural behavior at the joints between the precast segments can significantly affect the overall integrity, safety, and serviceability of the structure. In this study, therefore, the interface shear strength of high-strength precast members was investigated by performing push-off tests with the following variables: compressive strength of precast members, dry or wet joint, number and height of shear keys, joint width, filler type, curing temperature, and lateral compressive stress. The test results were analyzed to reveal the effect of each test variable on the joint shear strengths of the specimens. For instance, the failure loads were increased by 14–140%, depending on the lateral compressive stress, as the specified compressive strength of the precast members was increased from 80 to 150 MPa in the dry joints. The failure loads of the wet joints strongly depended on the strength of the filler rather than on that of the precast members and, as a result, the specimen with ultra-high-strength concrete filler was 46–48% stronger than those with high-strength mortar filler. The shear strengths of various joint types obtained from the test were further analyzed in comparison with the predictive equations of Japan Society of Civil Engineers (JSCE) and American Association of State Highway and Transportation Officials (AASHTO) with the aim of validating the appropriateness of these design provisions. In particular, an improved value of a coefficient in the JSCE equation is proposed to cover a range of compressive strengths in various precast members and filling materials.
Keywords: Cast-in-place construction; High strength mortars; Interface shear strength; Japan society of civil engineers; Joint shear strengths; Predictive equations; Structural behaviors; Ultra high strength concretes; Dry joint; High-strength concrete; Interface shear strength; Push-off test; Shear key; Ultra-high-performance concrete; Wet joint